Controlled dehydration improves the diffraction quality of two RNA crystals. (December 2016) - Park, HaJeung; Tran, Tuan; Lee, Jun; Park, Hyun; Disney, Matthew
Abstract Background Post-crystallization dehydration methods, applying either vapor diffusion or humidity control devices, have been widely used to improve the diffraction quality of protein crystals. Despite the fact that RNA crystals tend to diffract poorly, there is a dearth of reports on the application of dehydration methods to improve the diffraction quality of RNA crystals. Results We use dehydration techniques with a Free Mounting System (FMS, a humidity control device) to recover the poor diffraction quality of RNA crystals. These approaches were applied to RNA constructs that model various RNA-mediated repeat expansion disorders. Conclusion The method we describe herein could serve as a general tool to improve diffraction quality of RNA crystals to facilitate structure determinations.